2016
DOI: 10.1007/s00213-016-4422-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of non-alcoholic fatty liver disease and metabolic dysfunction in first episode schizophrenia and related psychotic disorders: a 3-year prospective randomized interventional study

Abstract: Our results support the importance of assessing the potential development of NAFLD in schizophrenia spectrum patients receiving antipsychotic medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 16 publications
0
26
1
1
Order By: Relevance
“…A recent study showed that the potential for NAFLD in schizophrenia patients receiving antipsychotic medication is higher. But this study examined the incidence of NAFLD using a randomized design in mostly middle-aged schizophrenia patients, and just looked at the effects of specific antipsychotics on Western people 8. In our study, we focused on young male patients with schizophrenia and investigated risk factors other than antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the potential for NAFLD in schizophrenia patients receiving antipsychotic medication is higher. But this study examined the incidence of NAFLD using a randomized design in mostly middle-aged schizophrenia patients, and just looked at the effects of specific antipsychotics on Western people 8. In our study, we focused on young male patients with schizophrenia and investigated risk factors other than antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed that the potential for NAFLD in first episode schizophrenia spectrum patients was increased after receiving antipsychotic medication for 3 years 8. Remarkable negative symptoms are common in the male patient with schizophrenia, which generally appear in early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…SGAs have been associated with chronic liver disease in patients with BD in a large observational study 161. During the first 3 years of antipsychotic treatment in patients with the first-episode schizophrenia, nonalcoholic fatty liver disease was associated with the presence of the major components of metabolic syndrome in an RCT 162. Liver function should be monitored in patients administered SGAs 163.…”
Section: Methodsmentioning
confidence: 99%
“…After 3 months and then yearly for 3 years, they (Morlan-Coarasa M J et al 2016. 34 ) calculated the NAFLD fibrosis score, fibrosis score and FLI at baseline. Finally, through their study they concluded that there is a potential related with the development of NAFLD with schizophrenic patients receiving anti-psychotic medication.…”
Section: Study Reports Related To the Risk Factors And Etiology Ofmentioning
confidence: 99%